AFIKS DERIVASI DALAM BAHASA INGGRIS DAN BAHASA TABARU (SUATU ANALISIS KONTRASTIF) - SIDETE, BEBI SUSANTO; LASUT, THERESIA M. C.; RANUNTU, GARRYN CHRISTIAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT The research entitled ‘Derivational Affixes in English and Tabaru Language (A Contrastive Analysis)’ written as a research to indentify, classify and analyze the derivational affixes in term of form, function and meaning in verb, noun, adjective and adverb. Beside that. the objectives of research are to find the differences of derivational affixes in English and Tabaru language by using O’grady’s (1987) theory and contrasting them by using Lado (1971) method. This data uses descriptive method. The English data were collected from several English textbooks, namely Contemporary Linguistic Analysis : An Introduction (1987) by O’grady and Jhon ; The descriptive Analysis of word (1946) by Nida and the data of Tabaru language were taken from three native speakers as informant who were born and lived in the land of Jailolo, precisely in Bukumatiti village. They were selected based on age, gender, intelligence, knowledge of language, communicative personality and acceptable social group. The results of this research show that the types of English derivational affixes are prefixes and suffixes; the types of Tabaru derivational affixes are prefixes, suffixes and confixes. The functions of both English and Tabaru language derivational affixes are whether to create new lexem that may change the part of speech or not. The differences Tabaru language has confixation but English doesn’t; negative meaning in Tabaru language based on suffixation process but in English though prefixation process; and form variation in English cannot attach to number base form but in Tabaru language it can attach. Key Words : Derivational affixes, English, Tabaru language.